Burkitt lymphoma after solid‐organ transplant: Treatment and outcomes in the paediatric PTLD collaborative. (1st December 2022) - Afify, Zeinab; Orjuela‐Grimm, Manuela; Smith, Christine Moore; Dalal, Mansi; Ford, James B.; Pillai, Pallavi; Robles, Joanna M.; Reddy, Sonika; McCormack, Sarah; Ehrhardt, Matthew J.; Ureda, Tonya; Alperstein, Warren; et al.
Summary: Burkitt lymphoma arising in paediatric post‐solid‐organ transplantation‐Burkitt lymphoma (PSOT‐BL) is a clinically aggressive malignancy and a rare form of post‐transplant lymphoproliferative disorder (PTLD). We evaluated 35 patients diagnosed with PSOT‐BL at 14 paediatric medical centres in the United States. Median age at organ transplantation was 2.0 years (range: 0.1–14) and age at PSOT‐BL diagnosis was 8.0 years (range: 1–17). All but one patient had late onset of PSOT‐BL (≥2 years post‐transplant), with a median interval from transplant to PSOT‐BL diagnosis of 4.0 years (range: 0.4–12). Heart ( n = 18 [51.4%]) and liver ( n = 13 [37.1%]) were the most frequently transplanted organs. No patients had loss of graft or treatment‐related mortality. A variety of treatment regimens were used, led by intensive Burkitt lymphoma‐specific French–American–British/Lymphomes Malins B (FAB/LMB), n = 13 (37.1%), and a low‐intensity regimen consisting of cyclophosphamide, prednisone and rituximab (CPR) n = 12 (34.3%). Median follow‐up was 6.7 years (range: 0.5–17). Three‐year event‐free and overall survival were 66.2% and 88.0%, respectively. Outcomes of PSOT‐BL patients receiving BL‐specific intensive regimens are comparable to reported BL outcomes in immunocompetent children. Multi‐institutional collaboration is feasible and provides the basis of prospective data collection to determine the optimal treatment regimen for PSOT‐BL.